The role of hysteroscopy in evaluating postmenopausal asymptomatic women with thickened endometrium - Giuseppe Trojano; Gianluca Raffaello Damiani; Vita Caroli Casavola; Rossella Loiacono; Antonio Malvasi; Antonio Pellegrino; Valeria Siciliano; Ettore Cicinelli; Maria Giovanna Salerno; Lorella Battini (Wolters Kluwer Medknow Publications, 2018)
Backgrounds and Aims: This study aims to compare hysteroscopic and histological findings in asymptomatic postmenopausal patients with thickened endometrium. Materials and Methods: A retrospective study involving case records of 295 asymptomatic postmenopausal women with a thickened endometrium >5 mm diagnosed at transvaginal ultrasound (TVS). Patients (women) underwent hysteroscopy with biopsy between 2009 and 2015, and they were followed up at National Cancer Institute of Bari and at University Hospital of Pisa. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of hysteroscopy were evaluated. Results: Inclusion criteria were TVS, hysteroscopy, and endometrial biopsy. When the hysteroscopic findings were normal, a sensitivity of 100%, specificity of 98.6%, PPV of 95.2%, and NPV of 100% were achieved. For polyps and myomas, we found 100%, 98.7%, 99.5%, and 100%, respectively. In case of endometrial hyperplasia, a sensitivity of 66.7%, a specificity of 100%, a PPV of 100%, and a NPV of 98.1% were achieved. For endometrial cancer hysteroscopy, sensitivity, specificity, PPV, and NPV were 100%, 99.6%, 75%, and 100%, respectively. Conclusions: Hysteroscopy allows an accurate diagnosis in benign endometrial pathology and suspect of malignant endometrial pathology in postmenopausal women with thickened endometrium.